The Effect of Cobalt, Vanadium Carbide and PKS Activated Carbon Addition on WC-Co Composite: A Study using Taguchi Method / Ahmad Aswad Mahaidin ...[et al.] - Mahaidin, Ahmad Aswad; Jaafar, Talib Ria; Budin, Salina; Selamat, Mohd Asri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
WC-Co, which is also known as cemented carbide, is widely used in metal cutting industry and wear related applications. Numerous studies have been made to improve the properties of the composite. Thus, this research paper is focusing on selection of WC-Co formulation using Taguchi method based on design factors such as percentage of cobalt, vanadium carbide and PKS activated carbon. The WC-Co composite is produced using powder metallurgy technique and sintered under nitrogen-based atmosphere. Based on the results obtained using Taguchi orthogonal array, it is found that WC-8Co-0.3C-0.4VC and WC-6Co-0.4VC are the optimized combination of levels for all the three control factor for hardness and flexural strength respectively.